Relationship between nurse staffing levels and nurse outcomes in community hospitals, Thailand - Nantsupawat,A. (Wiley-Blackwell, 2015)
© 2014 Wiley Publishing Asia Pty Ltd. A growing body of research has shown an association between nurse staffing levels and a range of nurse outcomes. There is little empirical research evaluating this relationship in Thailand. This study evaluated the influence of nurse staffing levels on outcomes among nurses. A cross-sectional survey design was conducted at 92 community hospitals using a stratified random sampling design across Thailand during May and July 2012. Questionnaires included items focusing on nurse staffing levels; job dissatisfaction and emotional exhaustion, both related to nurse retention; and needlestick and sharps injuries. The study sample comprised 1412 registered nurses who provided direct patient care. The findings showed that each additional patient per nurse was associated with an additional 5% of nurses reporting dissatisfaction in their job; 8% of nurses reporting high emotional exhaustion, and 4% of nurses reporting needlestick and sharps injuries. This study provides evidence of how nurse staffing levels result in nurse outcomes. Nurses are significant healthcare providers that directly affect quality of care and patient safety in hospitals. Improvement of nurse staffing levels holds promise for improving nurse outcomes in Thailand.